Nigeria's Digital Diaspora : Citizen Media, Democracy, and Participation - Kperogi, Farooq A., 1973- (Book collections on Project MUSE., 2020)
"In a disruptive media landscape characterized by the relentless death of legacy newspapers, Nigeria's Digital Diaspora shows that a country's transnational elite can shake its media ecosystem through distant online citizen journalism"--